4x - y = 3
y = 2x + 13
Substitute the second equation into the first equation:
4x - y = 3 [since y = 2x + 13, you can substitute (2x + 13) for "y" in the equation]
4x - (2x + 13) = 3 Distribute/multiply - into (2x + 13)
4x - 2x - 13 = 3
2x - 13 = 3 Add 13 on both sides
2x = 16 Divide 2 on both sides
x = 8
Now that you know x = 8, plug it into one of the equations to find y
y = 2x + 13
y = 2(8) + 13
y = 16 + 13
y = 29
x = 8, y = 29 or (8, 29)
[proof]
4x - y = 3
4(8) - 29 = 3
32 - 29 = 3
3 = 3
y = 2x + 13
29 = 2(8) + 13
29 = 16 + 13
29 = 29